Determination of 4‐bromo‐2, 5‐dimethoxy‐N‐[(2‐methoxyphenyl)methyl]‐benzeneethanamine (25B‐NBOMe) in serum and urine by high performance liquid chromatography with tandem mass spectrometry in a case of severe intoxication. Issue 7 (2nd September 2013) - Poklis, Justin L.; Nanco, Carol R.; Troendle, Michelle M.; Wolf, Carl E.; Poklis, Alphonse; Brandt, Simon D.
<x xml:space="preserve">Abstract</x> We present a case of 4‐bromo‐2, 5‐dimethoxy‐N‐[(2‐methoxyphenyl)methyl]‐benzeneethanamine (25B‐NBOMe), an N‐benzyl phenethylamines derivative, intoxication and a high performance liquid chromatography with tandem mass spectrometry (HPLC‐MS/MS) method for detection and quantification of 25B‐NBOMe. A 19‐year‐old male was found unresponsive with generalized grand mal seizure activity. On the second day of hospitalization, a friend admitted that the patient used 'some unknown drug' called 25B. Serum and urine collected were sent to the Virginia Commonwealth University Medical Center Toxicology Laboratory for analysis. An HPLC‐MS/MS method for the identification and quantification of 25B‐NBOMe using 2‐(2, 5‐dimethoxyphenyl)‐N‐(2‐methoxybenzyl)ethanamine (25H‐NBOMe) as the internal standard (ISTD) was developed. As this is a novel, single‐case presentation, an assay validation was performed prior to testing to ensure the reliability of the analytical results. The serum and urine specimens were determined to contain 180 pg/ml and1900 pg/ml of 25B‐NBOMe, respectively. Copyright © 2013 John Wiley & Sons, Ltd.